Analysis of foreign countries’ digital economy programs (Argentina, Brazil, India and Mexico) - V. I. Abramo; N. V. Malanicheva; I. A. Strelnikova (Управление)
The article is devoted to the analysis of foreign countries’ digital economy programs. The study considers Argentina, Brazil, India and Mexico cases. The authors assess the general state and level of digitalization of the economy of these countries and the national programs adopted for the digital economy development. Next, the article examines the first programs aimed at digitalization of the economy in foreign countries. The authors identify the main problems hindering the digitalization of the economy in Argentina, Brazil, India and Mexico, the characteristic features of each program and analyze the measures taken by states to improve their positions in the world in terms of the economy digitalization. As a result of the study, the authors found that the most successful from the economic development point of view are those countries where, firstly, the digitalization of the economy is supported by the current government, and, secondly, where the systems of institutions responsible for digitalization and communications between them are well developed. The article notes that common problems for states at present are the lack of a unified regulatory framework for the digitalization of the economy, as well as differences in regional development, which, of course, slows down the pace of progress in this direction.